ANALISIS PENGARUH KUALITAS PELAYANAN, HARGA, WORD OF MOUTH DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI BATIK DANII GAYA COLLECTION - Rika Puspaningrum (JURNAL EKOBIS DEWANTARA, 2022)
Abstract The reason for this thinking is to decide the impact of service quality, price, word of mouth and product quality on purchasing decisions. This strategy uses path analysis. The test used was 111 respondents. Collecting information by means of a questionnaire. The results show that service quality, price, word of mouth and product quality are simultaneously and partially affected by purchasing decisions, while word of mouth is not. Keywords: service quality ; price ; word of mouth ; product quality ; and purchasing decisions.